Trends in pediatric baseball and softball injuries presenting to emergency departments - Lee, A.; Farooqi, A.; Abreu, E.; Talwar, D.; Maguire, K. (The Physician and Sportsmedicine, 2023)
Background Millions of youth participate in baseball and softball in the United States and these youth account for a large number of pediatric sports injuries. This study sought to characterize annual, seasonal, and age-related trends in pediatric softball and baseball injuries presenting to the Emergency Department (ED).